2019
DOI: 10.3389/fpsyg.2019.01148
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Self-Kindness Into the Workplace: Exploring the Mediating Role of Self-Compassion in the Associations Between Attachment and Organizational Outcomes

Abstract: Research has shown that individual differences in adult attachment predict several organizational outcomes. However, little is known about the mechanism that underlies these associations. The current study examines whether self-compassion can serve as a potential mediator explaining the associations between individual differences in attachment and organizational outcomes. Four outcome measures were evaluated: job performance (HPQ; Kessler et al., 2003 ), organizational citizenship behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 101 publications
3
42
2
7
Order By: Relevance
“…We found non-significant associations for both avoidance and anxiety orientations in predicting OCB. These findings are not in line with previous work, which suggested that attachment orientations can predict prosocial behaviors such as OCB (e.g., Little et al, 2011;Richards and Schat, 2011;Reizer, 2019). We assume that the lack of significant associations between OCB and attachment orientations in the current study may stem from several causes, both theoretical and methodological.…”
Section: Discussioncontrasting
confidence: 98%
See 4 more Smart Citations
“…We found non-significant associations for both avoidance and anxiety orientations in predicting OCB. These findings are not in line with previous work, which suggested that attachment orientations can predict prosocial behaviors such as OCB (e.g., Little et al, 2011;Richards and Schat, 2011;Reizer, 2019). We assume that the lack of significant associations between OCB and attachment orientations in the current study may stem from several causes, both theoretical and methodological.…”
Section: Discussioncontrasting
confidence: 98%
“…Eighteen items assessed attachment anxiety (e.g., "I worry about being abandoned"), and 18 items assessed avoidance (e.g., "I prefer not to show a partner how I feel deep down"). Although Brennan et al (1998) demonstrated the orthogonality and discriminant validity of the anxiety and avoidance subscales, as reflected in previous studies (e.g., Geller and Bamberger, 2009;Reizer, 2019), the two subscale scores were significantly correlated in the current sample. For the current sample, Cronbach's αs were 0.91 for the anxiety items and 0.79 for the avoidance items.…”
Section: Attachment Orientationscontrasting
confidence: 51%
See 3 more Smart Citations